The Resilience of Caste through Yashica Dutt’s Coming Out as Dalit: A Memoir (2019) - Cherechés, Bianca (Complutense Journal of English Studies, 2024)
India, the largest democracy in the world, has experienced important social advances since its independence in 1947, such as the abolition of untouchability, one of the oldest forms of social segregation and discrimination whose major victims have been the Dalits. The situation of Dalits has undergone a series of changes in the second half of the 20th century due to various phenomena, including the industrialisation of India, the influential social work of Dalit activists and thinkers such as B. R. Ambedkar, and the passing of legal provisions for Dalits’ social inclusion, political emancipation and protection of rights. All these factors, along with a relative democratisation of education, have prompted this historically oppressed group to build a voice. Since then, Dalit literature has progressively become a platform through which past and present injustices committed against this community are exposed. Lately, the impact that democracy has had on the lives of Dalits has been a questioned topic and Yashica Dutt’s Coming Out as Dalit: A Memoir (2019) is an interesting gateway to it. The author’s gender and geographical position and her particular experience with ‘Dalithood’ result in an unusual but necessary insight into Dalits’ state of affairs in contemporary India. Thus, using Dutt’s memoir as a lens, this paper aims to examine the conditions that led to the perpetuation of a learned helplessness among Dalits, the shortcomings of Sanskritisation as an escape strategy from casteist stigma and the implications of the reservation system set for India’s Depressed Castes.